Golimumab, a Human Anti–Tumor Necrosis Factor Monoclonal Antibody, Injected Subcutaneously Every 4 Weeks in Patients With Active Rheumatoid Arthritis Who Had Never Taken Methotrexate: 1‐Year and 2‐Year Clinical, Radiologic, and Physical Function Findings of a Phase III, Multicenter, Randomized, Double‐Blind, Placebo‐Controlled Study1. Issue 11 (28th October 2013) - Emery, Paul; Fleischmann, Roy M.; Doyle, Mittie K.; Strusberg, Ingrid; Durez, Patrick; Nash, Peter; Amante, Eric; Churchill, Melvin; Park, Won; Pons‐Estel, Bernardo; Xu, Weichun; Xu, Stephen; et al.
<x xml:space="preserve">Abstract</x> Objective To assess 2‐year golimumab efficacy/safety in patients with active rheumatoid arthritis (RA) who had never taken methotrexate (MTX). Methods RA patients who had never taken MTX (n = 637) were randomized (1:1:1:1) to placebo + MTX (group 1), golimumab 100 mg + placebo (group 2), golimumab 50 mg + MTX (group 3), or golimumab 100 mg + MTX (group 4) every 4 weeks. Nonresponders based on week 28 swollen/tender joint counts changed treatment as follows: group 1 added golimumab 50 mg, group 2 added MTX, group 3 increased golimumab to 100 mg, and group 4 had no change. Most group 1 patients (85%) initiated golimumab 50 mg + MTX at week 28 or subsequently at week 52. After the last patient completed week 52 and blinding was broken, the investigator could escalate golimumab to 100 mg and/or adjust MTX. The co–primary end points (week 24 American College of Rheumatology criteria for 50% improvement [ACR50] response and week 52 change in Sharp/van der Heijde score [SHS]) have been published previously. We now detail week 52 major secondary end points (Health Assessment Questionnaire [HAQ] disability index [DI] scores and SHS among patients with a baseline C‐reactive protein [CRP] level >1.0 mg/dl) and week 104 findings. Results At week 52 for combined groups 3 and 4 versus group 1, the respective proportions of patients achieving ACR20 and ACR50 responses were 63.2% versus 51.9% (P = 0.017) and 45.3% versus 35.6% (P = 0.044). Respective week 52 mean HAQ DI improvements were 0.70 versus 0.58 (P = 0.053); mean SHS changes were 0.41 versus 1.37 (P = 0.006) among all patients and 0.74 versus 2.16 (P = 0.003) in patients with a CRP level >1.0 mg/dl. Improvements were maintained through week 104. Golimumab + MTX for 2 years yielded statistically less radiographic progression than initial MTX or golimumab 100 mg monotherapy. Golimumab safety profiles through weeks 24, 52, and 104 were generally consistent with those observed in other golimumab studies. Conclusion In RA patients who had never taken MTX, up to 2 years of golimumab + MTX yielded sustained improvements in clinical signs/symptoms, physical function, and radiographic progression.